Double deletion of a chromosome 21 inserted in a chromosome 22 in an azoospermic patient. Issue 9 (20th August 2015) - Marquet, Valentine; Bourgeois, Dominique; De Mas, Philippe; Bouneau, Laurence; Vigouroux‐Castera, Adeline; Molignier, Romain; Calvas, Patrick
Key Clinical Message: We report on a phenotypically normal 41‐year‐old azoospermic man with a 45 chromosomes karyotype including one normal chromosome 21, one normal chromosome 22, and a der(22)ins(22;21). Array CGH showed a 1.8 Mb terminal deletion of bands 21pter to 21q21.1 and a 341 kb terminal deletion on band 21q22.3. Abstract : We report on a phenotypically normal 41‐year‐old azoospermic man with a 45 chromosomes karyotype including one normal chromosome 21, one normal chromosome 22, and a der(22)ins(22;21). Array CGH showed a 1.8 Mb terminal deletion of bands 21pter to 21q21.1 and a 341 kb terminal deletion on band 21q22.3.